The Concept of Scientific and Religious Truth (Case Study of Scientific and Religious Truth in Setu Wetan Village) - Indi Millatul Maula; Hanipah Hanipah; Alifiatun Asyifah (Journal of Social Research, 2023)
This research aims to provide a more comprehensive understanding of perceptions of truth in the community of Setu Wetan Village, especially in a religious context, and how this view influences the way they seek the truth. The research was conducted in the setting of a district in Cirebon Regency. Primary data was obtained through in-depth interviews with the people of Setu Wetan Village as the main respondents. Data analysis was carried out descriptively and qualitatively with the aim of providing a comprehensive picture to the reader. The results of the analysis show that science has an inseparable role in the lives of religious communities in the village. Therefore, the development of education and knowledge is very important in improving the quality of life of the people in the Village. The research provides insights into the perceptions of truth in the community of Setu Wetan Village and how it influences their way of seeking the truth. The study emphasizes the importance of science and education in the lives of religious communities in the village. The research also highlights the relevance of local knowledge and wisdom in disaster management in Indonesia.